THE FACTORS THAT CAUSE PRODUCT DEFECT ON MOFFEE COFFEE STORE MANADO - Putra, Adjie M. Syah; Saerang, David P. E.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The purpose of this research is to analyze factors that cause product defection on the product making processes at Moffee Coffee Store were the factors that contribute to the defection of the product need to categorize based on the affection of the factors in order to understand the real problem of product defection. This research conducting a qualitative approach with descriptive analyses. Therefore, this research designing the methodological processes of research with Fishbone diagram that can elaborate factors that caused product defection with quantification value to determined affection causes of the product defection and through the results of the interview this research conducting further interviews for the better conclusions with Pareto analysis. The findings indicate the factors that affect product defection are Man Power, Method, Management, and Machine. The most significant factor of defection at Moffee Coffee Store products is material stock errors, that is why Moffee Coffee Store needs to replace them with lower quality ingredients or eliminate one ingredient even if it is not following operational standards. The results of the Pareto analysis show the different and more in-depth details related to the dominant factors that cause product defect at the Moffee Coffee Store as human resource factors, especially on the durability of their employees work. The use of qualitative methods in this research is sufficient to limit researchers to use other statistical analytical tools because of different types of data that cannot be quantified and not conducting surveying to customers to collect their opinions about the factors that they think can be the root of the problem of product defection on the Moffee Coffee Store.Keywords: Product defection, Moffee Coffee Store, Fishbone, Pareto analysis